ESTELL: A Quasi‐Toroidally Symmetric Stellarator. Issue 6 (18th March 2013) - Drevlak, M.; Brochard, F.; Helander, P.; Kisslinger, J.; Mikhailov, M.; Nührenberg, C.; Nührenberg, J.; Turkin, Y.
Abstract This work presents the physics design for a simple quasi‐axially symmetric stellarator. A plasma configuration described by a modest number of Fourier coefficients was found to establish this symmetry with good accuracy. The low rotational transform results in a relatively simple coil set exhibiting low curvatures and comfortable clearance between adjacent coils. As another consequence, the maximum achievable plasma pressure will be limited to about 0.5%. An experiment along the lines proposed would allow an exploration of the confinement properties of a quasi‐axially symmetric configuration. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)